PROBLEMS OF OBJECTIVE PREREQUISITES IN CASES OF CHALLENGING THE LEGALITY OF NORMATIVE LEGAL ACTS IN ADMINISTRATIVE PROCEDURE - Dilbandyan, Oksana (State and Law, 2023)
This article is dedicated to the object of proceedings on challenging the legality of normative legal acts. Considering that the proceedings on challenging the legality of normative legal acts are of high public importance, this study reveales the features that characterize the object of the proceedings on disputing the legality of normative legal acts and the limits of object. In addition, this paper discusses a number of issues related to the object of disputes over the validity of normative legal acts, such as determining the nature of the challenged act.